IL-33/ST2L Signaling Provides Neuroprotection Through Inhibiting Autophagy, Endoplasmic Reticulum Stress, and Apoptosis in a Mouse Model of Traumatic Brain Injury - Gao, Yuan; Zhang, Ming-yang; Wang, Tao; Fan, Yan-yan; Yu, Lin-sheng; Ye, Guang-hua; Wang, Zu-feng; Gao, Cheng; Wang, Hao-chen; Luo, Cheng-liang; Tao, Lu-yang (Frontiers in Cellular Neuroscience, 2018)
Interleukin-33 (IL-33) is a member of the interleukin-1 cytokine family and an extracellular ligand for the orphan IL-1 receptor ST2. Accumulated evidence shows that the IL-33/ST2 axis plays a crucial role in the pathogenesis of central nervous system (CNS) diseases and injury, including traumatic brain injury (TBI). However, the roles and molecular mechanisms of the IL-33/ST2 axis after TBI remain poorly understood. In this study, we investigated the role of IL-33/ST2 signaling in mouse TBI-induced brain edema and neurobehavioral deficits, and further exploited underlying mechanisms, using salubrinal (SAL), the endoplasmic reticulum (ER) stress inhibitor, and anti-ST2L. The increase in IL-33 level and the decrease in ST2L level at injured cortex were first observed at 24 h post-TBI. By immunofluorescent double-labeled staining, IL-33 co-localized in GFAP-positive astrocytes, and Olig-2-positive oligodendrocytes, and predominantly presented in their nucleus. Additionally, TBI-induced brain water content, motor function outcome, and spatial learning and memory deficits were alleviated by IL-33 treatment. Moreover, IL-33 and SAL alone, or their combination prevented TBI-induced the increase of IL-1β and TNF-α levels, suppressed the up-regulation of ER stress, apoptosis and autophagy after TBI. However, anti-ST2L treatment could significantly invert the above effects of IL-33. Together, these data demonstrate that IL-33/ST2 signaling mitigates TBI-induced brain edema, motor function outcome, spatial learning and memory deficits, at least in part, by a mechanism involving suppressing autophagy, ER stress, apoptosis and neuroinflammation.